2017
DOI: 10.1136/vr.j5505
|View full text |Cite
|
Sign up to set email alerts
|

Porcine circovirus type 3 in the UK

Abstract: A novel porcine circovirus distantly related to known circoviruses is associated with porcine dermatitis and nephropathy syndrome and reproductive failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 6 publications
0
31
1
2
Order By: Relevance
“…It was initially found in 2016 in tissues of swine affected by porcine dermatitis and nephropathy syndrome (PDNS), reproductive failure, and cardiac and multisystemic inflammation (Palinski et al, 2017;Phan et al, 2016) in the USA. Subsequently, other reports from Europe (Collins, McKillen, & Allan, 2017;Faccini et al, 2017;Franzo, Legnardi, Hjulsager et al, 2018;Stadejek, Wo zniak, Miłek, & Biernacka, 2017), Asia Ku et al, 2017;Kwon, Yoo, Park, & Lyoo, 2017;Shen et al, 2017;Zhai et al, 2017;Zheng et al, 2017) and South America (Tochetto et al, 2017) described the presence of PCV-3 genome in tissue samples or sera from pigs with different clinical presentations as well as in healthy animals.…”
Section: Introductionmentioning
confidence: 99%
“…It was initially found in 2016 in tissues of swine affected by porcine dermatitis and nephropathy syndrome (PDNS), reproductive failure, and cardiac and multisystemic inflammation (Palinski et al, 2017;Phan et al, 2016) in the USA. Subsequently, other reports from Europe (Collins, McKillen, & Allan, 2017;Faccini et al, 2017;Franzo, Legnardi, Hjulsager et al, 2018;Stadejek, Wo zniak, Miłek, & Biernacka, 2017), Asia Ku et al, 2017;Kwon, Yoo, Park, & Lyoo, 2017;Shen et al, 2017;Zhai et al, 2017;Zheng et al, 2017) and South America (Tochetto et al, 2017) described the presence of PCV-3 genome in tissue samples or sera from pigs with different clinical presentations as well as in healthy animals.…”
Section: Introductionmentioning
confidence: 99%
“…Like PCV2, there are two major open reading frames (ORFs) in the genome of PCV3: ORF1 encodes proteins involved in viral replication (Rep) and ORF2 encodes a major structural protein, the capsid protein (Cap) 25. PCV3 sequences were detected widely in the USA,21 China,26, 27, 28 Brazil,29 Thailand,30 Korea,23 and many European countries,22, 31, 32, 33, 34 including Poland, Italy, Spain, Denmark, Germany, the UK among others. The PCV3 that was first identified in the USA was more closely related to canine circovirus although with weak bootstrap support 21.…”
Section: Introductionmentioning
confidence: 99%
“…Almost concomitantly, another research group in the United States found PCV3 in tissues of sows with PDNS, as well as in mummified foetuses aborted from such sows (Palinski et al, 2017). Subsequently, PCV3 was reported in China, Poland, South Korea, Brazil, Italy and the UK (Faccini et al, 2017;Fu et al, 2017;Kwon, Yoo, Park, & Lyoo, 2017;Stadejek, Wozniak, Milek, & Biernacka, 2017;Tochetto et al, 2017;Ku et al, 2017;Collins, McKillen, & Allan, 2017). The PCV3 genome comprises a circular single-stranded DNA of 2,000 bp in length, consisting of two major open reading frames (ORFs).…”
Section: Introductionmentioning
confidence: 99%